Information security awareness among youth in Klang Valley: a focus group discussion - Omar, Siti Zobidah; Kovalan, Krishnapriyaa; Bolong, Jusang (Human Resource Management Academic Research Society, 2020)
Issues on the lack of understanding on the awareness of information security among the Internet user has become central debate now a day. User’s ignorance and negligence towards awareness of information security, may lead to being the victim of cybercrime syndicates. This can be clearly seen through the increase of number in cybercrime statistics in Malaysia. Internet users has been scammed, cyberbullying and faced loss amount of money due to their unawareness of information security. The purpose of this study is to look at the youth understanding of information security awareness. Based on the focus group discussion with a total of 20 informants among youth, this research try to obtain the youth perspective and understanding on information security awareness. Using convenience sampling, youth were chosen as informants since they are mostly engaged with new media compared to other age groups. Discussions were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results show that there were few themes emerge on the awareness of information security, such as secure password usage, information sharing, safe online shopping website, and safe online banking website. Generally, most of the youth have a basic knowledge on information security awareness, particularly on having a secure password usage and information sharing. This study on the other hand, creates awareness on the important of information security, thus educated them to become a safe Internet user. Future study emphasizing on the government’s role in regulating the cybercrime issues and educating smart device users towards safe Internet usage is recommended.